Pertanggungjawaban Pidana Pelaku Kekerasan Seksual yang Menyalahgunakan Jabatan hingga Mengakibatkan Korban Bunuh Diri dalam Perspektif Undang-Undang Tindak Pidana Kekerasan Seksual - Niczem Alfa Wengen; Roy Marthen Moonti; Ibrahim Ahmad (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
This study analyzes the criminal liability of perpetrators of sexual violence who abuse their position of authority, resulting in the victim's suicide, based on Law Number 12 of 2022 concerning the Crime of Sexual Violence. The research employs a normative legal method using statutory, conceptual, and case approaches. Primary legal materials consist of legislation and court decisions, while secondary legal materials are derived from books, scholarly journals, and relevant research. The findings indicate that criminal liability must be established through proof of the elements of sexual violence, abuse of position or power relations, the perpetrator's culpability, and the causal relationship between the perpetrator's conduct, the victim's psychological trauma, and the resulting death. Article 6(c) of the Law on the Crime of Sexual Violence serves as the primary legal basis for criminal prosecution, while Article 15 may be applied as an aggravating circumstance when the perpetrator is a superior, employer, public official, or organizational administrator whose actions result in severe psychological harm or death. The victim's suicide does not automatically establish or negate the causal relationship. Such causation must be supported by expert testimony, medical records, electronic evidence, psychological autopsy findings, family testimony, and a chronology of the victim's psychological deterioration. Therefore, criminal judgments should be based on the convergence of lawful, relevant, authentic, and corroborative evidence to ensure victim protection, legal certainty, the presumption of innocence, and substantive justice. Law enforcement should also guarantee restitution for the victim's family and promote institutional reforms to prevent similar offenses from recurring.